Penggunaan Metode Bermain Media Question Card Pada Pembelajaran Teks Deskripsi - Taufan Hadi; Nikmatul Izzah (CV. Satria Jaya, 2024)
This study aims to describe the use of learning methods playing Question Card media as an alternative solution to increase student motivation and learning activeness in Indonesian Language Lessons on Descriptive Text material in VII grade junior high school students. The method used in this research is qualitative descriptive method through in-depth interviews, observation, and documentation. The results of the study found that the use of question card media game method can motivate students to be actively involved in learning. This method places students as the center of learning and the teacher acts as a facilitator. The question card media game method also trains students' skills in communication, collaboration and creative thinking. Based on the formative test results obtained, namely 21 students or around 87.5% of students obtained scores above the minimum completeness criteria and only 3 students or 12.5% of students still obtained scores below the minimum completeness criteria, cooperative learning using the question card media game method is believed to be used as an interactive method in learning at the Junior High Level. This method can also be applied to various subjects by adjusting the characteristics of the material, the characteristics of the students and the characteristics of the class where this method will be used.